Digital Pocketbook Education with a Nurse-Led Approach to Improve Hypertension Self-Management in Primary Care (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Hypertension remains a major global public health problem, contributing significantly to morbidity and mortality associated with cardiovascular diseases. Effective management requires optimal self-management; however, patients’ adherence and understanding remain limited in primary healthcare settings. Despite the growing use of digital health interventions, simple and accessible educational media integrated with nurse-led approaches are still underutilized in community-based settings. This community service program aimed to evaluate the effectiveness of digital pocketbook-based education using a Nurse-Led Self-Management approach in improving knowledge and self-management awareness among hypertensive patients in a primary healthcare facility (Klinik Pratama). A total of 30 participants were involved in structured educational sessions and individual mentoring. The program was implemented through three stages: preparation, implementation, and evaluation. Data were collected using a pre-test and post-test approach and analyzed descriptively to assess changes in participants’ knowledge. The results showed a substantial improvement in participants’ knowledge, with the proportion of participants categorized as having good knowledge increasing from 30% before the intervention to 80% after the intervention. In addition, participants demonstrated increased awareness and motivation to adhere to recommended self-management practices, including medication adherence and routine blood pressure monitoring. This study highlights that integrating digital pocketbook-based education with a nurse-led approach is a practical and scalable strategy to enhance patient engagement and self-management in primary healthcare. This model has strong potential for wider implementation in community-based chronic disease management programs.